The Manipulation of Molecular Aggregation Behavior: Underwater Superoleophobic/Underoil Superhydrophobic Gels from the Same Matrix for Oil/Water Separation. Issue 11 (4th May 2020) - Hu, Junyi; Ding, Cong; Wang, Caoyu; Cao, Feifei; Zheng, Xinsheng; Zhang, Geng
Abstract: Manipulating the molecular aggregation behavior plays an important role in many fields. Here, by manipulating the molecular aggregation behavior, it is the first time that the same benzoxazine molecule is used to synthesize two kinds of gel materials with underwater superoleophobic and underoil superhydrophobic properties. Meanwhile, these materials are successfully used to separate surfactant‐stabilized water‐in‐oil and oil‐in‐water emulsions. The relationship between the surface properties and molecular aggregation behavior is analyzed. Controlling molecular aggregation behavior is essential to allow the molecules reach the most stable state spontaneously (where the Gibbs free energy is the smallest under constant temperature and pressure) under different environmental conditions. This research may open a new pathway to construct different functional materials by using the same molecule, and also provide a basis for other fields to achieve various applications by manipulating the molecular aggregation behaviors. Abstract : Under certain conditions, the molecules can only adopt the corresponding aggregation behavior to achieve the most stable aggregation manner, thereby exhibiting unique surface properties. Owing to this motivation, benzoxazine monomers are used as model molecules, their surrounding environmental conditions are changed, aggregation behavior is manipulated, and gel materials with different wettability from the same matrix are obtained.